2009
DOI: 10.1002/ps.1743
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and field cage studies on female‐targeted attract‐and‐kill bait stations for Anastrepha suspensa (Diptera: Tephritidae)

Abstract: A long-lasting, female-targeted fruit fly bait station, such as the one developed herein, could provide a cost-effective option for fruit fly population suppression that would be an important tool in tephritid pest management and control. Additional studies are needed to demonstrate efficacy against wild fruit fly populations and determine deployment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…A need to develop improved lures and “attract-and-kill” devices including bait stations for successful fruit fly control has already been recognized (IAEA, 2007; Heath et al 2009). The so-called Papaya Leaf Mimic (PLM), which represents a supernormal visual stimulus of papaya foliage, was developed in Hawaii in response to an imperative need to protect GF-120 against rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…A need to develop improved lures and “attract-and-kill” devices including bait stations for successful fruit fly control has already been recognized (IAEA, 2007; Heath et al 2009). The so-called Papaya Leaf Mimic (PLM), which represents a supernormal visual stimulus of papaya foliage, was developed in Hawaii in response to an imperative need to protect GF-120 against rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…The outside face of the trap (the snap-on cap) was covered with green tape to provide a visual cue, and it contained a 1.5-cm-diameter hole in the center to provide a point source release of volatiles from test substrate and a point of entry for the ßies. A wax matrix bait station strip (2.54 cm by 6.35 cm by 4 mm thick; Heath et al 2009) with 1% granulated sugar as feeding stimulant, 1% methomyl (Lannate, 90% [AI]; DuPont Ag Products, Wilmington, DE) as toxicant, and green food color as visual cue was placed in each trap to retain ßies that had entered. All ßies were sexually mature (11Ð13 d) and had been protein-starved for 24 h before the test.…”
Section: Methodsmentioning
confidence: 99%
“…Capture of female insects beside males, on the other hand, would provide a better opportunity for: 1) more precise monitoring, leading to more accurate decision-making on timing of control strategies against a given pest species (Wall, 1985); 2) more efficient mass trap-ping by direct population reduction catching gravid females (Bakke and Lie, 1985), as reported, among others, for Ceratitis capitata Wied. (Diptera: Tephritidae) (Katsoyannos et al, 1999); 3) the application of the lure-and-kill method, as reported for example in Anastrepha suspensa Loew (Diptera: Tephritidae) (Heath et al, 2009); 4) efficacy assessment of the sterile male technique by determining egg sterility of captured females (e.g. in C. capitata, Miranda et al, 2001).…”
mentioning
confidence: 99%